PENINGKATAN KINERJA GURU MELALUI MUTASI DI SD ISLAM AL AZHAR 1 KEBAYORAN BARU - EE Junaedi Sastradiharja; Ahmad Zain Sarnoto; Muhammad Dhiya Habibi (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2022)
The conclusion of this study shows that teacher performance can be improved through mutations with several findings, including: 1) the implementation of teacher transfers at SD Islam Al Azhar 1 Kebayoran Baru can be said to be an effective step because in terms of quality, the impact of the implementation of the transfer of positions has improve the quality of employee performance and achieve all the goals that have been set and 2) the implementation of teacher transfers at Al Azhar Islamic Elementary School 1 Kebayoran Baru has been successful because in its implementation, they obtain the goals and functions as planned and oriented to the applicable rules, such as: refreshment from boredom at work, spreading goodness and achievements in other places, increasing discipline, eliminating the stigma of being good at cages, establishing friendships between teachers, effectiveness in optimizing time and cost efficiency, means of assessing teacher loyalty to schools and foundations, and being a means to k coaching for teachers who have problems so that the teacher returns to focus on work. The method used in this research is descriptive analysis. Methods of data collection using interview techniques, documentation, and observation. Data analysis uses data reduction, data presentation, and drawing conclusions. While the approach used is a qualitative approach